2020
DOI: 10.1027/0227-5910/a000653
|View full text |Cite
|
Sign up to set email alerts
|

Youth Suicide Bereavement and the Continuum of Risk

Abstract: Abstract. Background: There is limited research investigating the risks for young friends exposed to the suicide of peers. Aims: This study aimed to better understand the impact of suicide bereavement on rural young people. Method: Participants in this a mixed-method study were 18 young people who had been exposed to a friend's suicide and who resided in rural Australia. Quantitative data were analyzed with SPSS and qualitative data were analyzed thematically. Results: Participants reported high levels of depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…Two mixed-methods studies were included in this review. Time since bereavement ranged between 15 and 38 months in one study ( 53 ) and was not reported in the other study ( 76 ). Both studies ( 53 , 76 ) had a sample size of N = 18, with a slightly lower proportion of men compared to women.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Two mixed-methods studies were included in this review. Time since bereavement ranged between 15 and 38 months in one study ( 53 ) and was not reported in the other study ( 76 ). Both studies ( 53 , 76 ) had a sample size of N = 18, with a slightly lower proportion of men compared to women.…”
Section: Resultsmentioning
confidence: 87%
“…Time since bereavement ranged between 15 and 38 months in one study ( 53 ) and was not reported in the other study ( 76 ). Both studies ( 53 , 76 ) had a sample size of N = 18, with a slightly lower proportion of men compared to women. One sample comprised friends of the deceased ( 76 ), while the other included partners, parents, siblings and offspring ( 53 ).…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Although the prevalence of suicide attempts among young people peaks during adolescence, the prevalence of death by suicide increases steadily into young adulthood (Carballo et al, 2020). For example, in Australia, suicide has been reported as the leading cause of death among young people for the past decade (Australian Bureau of Statistics [ABS], 2020; Bartik et al, 2020). The number of deaths by suicide and standardized death rates for suicide among young people increased across all Australian states and territories.…”
Section: Suicide Is a Universal Issuementioning
confidence: 99%
“…Suicide is not only a tragic end of life but may also be the beginning of a very challenging life for those left behind. Contemporary estimates highlight the profound impact of each suicide on about 60 suicide-loss survivors (SLSs), referring to individuals exposed to the suicide, including family members, friends, co-workers, classmates, or therapists [ 1 , 2 , 3 , 4 ]. Thus, between 48 million to 500 million people could be considered SLSs annually [ 5 ].…”
Section: Introductionmentioning
confidence: 99%